INTERNATIONAL PROTOCOL. DIPLOMATIC CONVERSATION AND CORRESPONDENCE ETIQUETTE AND DIPLOMATIC - Ahmedov Azimjon; Ibragimov Giyosiddin (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article you will learn about International etiquette and diplomatic protocol.